A triangular shell element for geometrically nonlinear analysis - Rezaiee-Pajand, M.; Arabi, E.; Masoodi, Amir R. (Acta mechanica, 2018)
In this paper, a geometrically nonlinear formulation for a six-node triangular shell element is proposed. Total Lagrangian formulation is utilized to consider large displacements and rotations in the shell analysis. To avoid shear and membrane locking, a proper interpolation function for the strain field is implemented. Both algorithm and flowchart of the nonlinear solution, which are utilized in the author’s computer program, are presented. To validate the suggested formulation, several popular benchmark problems are solved. Moreover, the obtained results are compared with those of the other well-known elements. Findings demonstrate the ability of the suggested shell element.